UNIVERSITIES AS GENERATOR FOR REGIONAL DEVELOPMENT - Andrey V. Belotserkovsky (Moscow Polytechnic University, 2016)
Some systematic challenges for Russian higher education are considered. Several ways of meeting the challenges are proposed in order to turn regional universities into the centers of regional development.